Effectiveness of sub-Tenon's block in pediatric strabismus surgery - Tuzcu,Kasim (2015)
ABSTRACTBACKGROUND AND OBJECTIVES: Strabismus surgery is a frequently performed pediatric ocular procedure. A frequently occurring major problem in patients receiving this treatment involves the oculocardiac reflex. This reflex is associated with an increased incidence of postoperative nausea, vomiting, and pain. The aim of this study was to investigate the effects of a sub-Tenon's block on the oculocardiac reflex, pain, and postoperative nausea and vomiting.METHODS: 40 patients aged 5-16 years with American Society of Anesthesiologists status I-II undergoing elective strabismus surgery were included in this study. Patients included were randomly assigned into two groups by using a sealed envelope method. In group 1 (n = 20), patients did not receive sub-Tenon's anesthesia. In group 2 (n = 20), following intubation, sub-Tenon's anesthesia was performed with the eye undergoing surgery. Atropine use, pain scores, oculocardiac reflex, and postoperative nausea and vomiting incidences were compared between groups.RESULTS: There were no significant differences between groups with regard to oculocardiac reflex and atropine use (p > 0.05). Pain scores 30 min post-surgery were significantly lower in group 2 than in group 1 (p < 0.05). Additional analgesic needed during the postoperative period was significantly lower in group 2 compared to group 1 (p < 0.05).CONCLUSIONS: In conclusion, we think that a sub-Tenon's block, combined with general anesthesia, is not effective and reliable in decreasing oculocardiac reflex and postoperative nausea and vomiting. However, this method is safe for reducing postoperative pain and decreasing additional analgesia required in pediatric strabismus surgery.